A Historical Review of the Comparative Study of Mohism and Christianity during the Late Qing and Republican China Periods - Pang, Wing Yin (Religions, 2024)
This study provides a fresh understanding of the historical development shaping comparative studies between Christianity and Mohism during the late Qing and Republican China periods. It traces the foundation of these studies to both the idea that ‘Western knowledge originated from Mohism’ and to the Mohism studies by the Qian-Jia School 乾嘉學派 during the Qing Dynasty. This study spotlights the groundbreaking proposition by Zou Boqi 鄒伯奇 in 1844, who first suggested that Western knowledge, including Christianity, originated from Mohism, a widely accepted view among Chinese literati. The article then explores the paradigm shift initiated by Liang Qichao 梁啓超, influenced by Sun Yirang 孫詒讓 and his Mozi Jiangu 墨子閒詁 (The Works of Mozi with Commentaries), which broadened the comparative perspective. The significant influence of the Qian-Jia School’s Mohism studies on both Chinese and non-Chinese scholars is analyzed, along with the diverse approaches and contributions of key figures like Joesph Edkins, James Legge, Ernst Faber, Alexandra David-Néel, Daisetz Teitaro Suzuki, Huang Zhiji 黃治基, Wang Zhixin 王治心, Zhang Chunyi 張純一, Mei Yi-Pao 梅貽寶, and Wu Leichuan 吳雷川. The article underscores these scholarly groups’ dynamic interplay and varied objectives, shaping a vibrant and contentious academic landscape.